Orang Yang Berilmu Pengetahuan Menurut Alquran; (Term-Term Kecendekiaan Melalui Kajian Tematik) - Mubarak Mubarak; Isna Radiyah (AZKIYA, 2021)
Knowledge is very important, in addition to the primacy, it is the command of Allah. Humans have glory because of the science of knowledge. Therefore, the emphasis on the importance of knowledge for people, especially Muslims, has been there since the beginning of Islam revealed to the Prophet Muhammad. Science is meant obtained through the intermediary of the ability to read and write, or in different meanings through careful observation of the situation surrounding human life. This short article will discuss people with knowledge according to a review of the Quran as an effort to find the term-term intellectual according to the thematic study. The results of the study found that the science in the study of Islam has been found to have definition and foundation. There is also an explanation in the Quran about the people of knowledge and the reasons for revelation with regard to the tribunal of science. In fact, a variety of term similar texts with our intelligence as a form of real knowledgeable person is found in the term-term: Ûlû al-‘Ilm, al-Râsikhûn fī al-‘ilm, Ûlû al-Albâb, al-‘Âlimûn and al-‘Ulamâ.